Dependence or constraints? Cash transfers, labor supply and the process of development - Diego Alejandro Vera Cossio (Institute for Advanced Development Studies (INESAD), 2017)
In this study, I use the timing and eligibility criteria of a large-scale conditional cash transfer program in Bolivian public schools to identify the efect of the program on adults' labor supply. I find that adult females increase their labor supply due to the program, mostly through self-employment. To understand these results, I sketch a simple theoretical framework of selection into employment that introduces fixed costs to work and imperfections in capital markets, two main features of the process of development. In this environment, households select into employment only if they are able to self-finance the fixed costs. I derive additional predictions that are empirically tested. First, the positive treatment efects should manifest at the extensive and not the intensive margin. Estimating treatment efects along the cumulative density function of work hours/week, I find that the efects on labor supply come exclusively from the extensive margin. Second, the efects of an income shock should be stronger when capital market frictions are more salient. Using baseline data for the supply of financial services at the municipality level as a third diference, I find that the efects on labor supply are higher for women in more credit-constrained areas. I compare these results with compelling alternative explanations such as in creases in local aggregate demand induced by the program and the relaxation of time constraints for mothers due to the condition component of the program. I find no evidence supporting these two alternative mechanisms. Overall, the results suggest that after considering the role of credit and labor market frictions, the first step in limbing the ladder of development is to cover come the barriers households face in simply starting to work.
Keywords: D13; J46; J21; J22; O12; O18; 330; Labor supply; poverty traps; gender; conditional cash transfers